Relationships and genetic consequences of contrasting modes of speciation among endemic species of Robinsonia (Asteraceae, Senecioneae) of the Juan Fernández Archipelago, Chile, based on AFLPs and SSRs. Issue 1 (10th September 2014) - Takayama, Koji; López‐Sepúlveda, Patricio; Greimler, Josef; Crawford, Daniel J.; Peñailillo, Patricio; Baeza, Marcelo; Ruiz, Eduardo; Kohl, Gudrun; Tremetsberger, Karin; Gatica, Alejandro; Letelier, Luis; Novoa, Patricio; et al.
Summary This study analyses and compares the genetic signatures of anagenetic and cladogenetic speciation in six species of the genus Robinsonia (Asteraceae, Senecioneae), endemic to the Juan Fernández Islands, Chile. Population genetic structure was analyzed by amplified fragment length polymorphism (AFLP) and microsatellite (simple sequence repeat, SSR) markers from 286 and 320 individuals, respectively, in 28 populations. Each species is genetically distinct. Previous hypotheses of classification among these species into subgenera and sections, via morphological, phytochemical, isozymic and internal transcribed spacer (ITS) data, have been confirmed, except that R. saxatilis appears to be related to R. gayana rather than R. evenia. Analysis of phylogenetic results and biogeographic context suggests that five of these species have originated by cladogenesis and adaptive radiation on the older Robinson Crusoe Island. The sixth species, R. masafuerae, restricted to the younger Alejandro Selkirk Island, is closely related to and an anagenetic derivative of R. evenia from Robinson Crusoe. Microsatellite and AFLP data reveal considerable genetic variation among the cladogenetically derived species of Robinsonia, but within each the genetic variation is lower, highlighting presumptive genetic isolation and rapid radiation. The anagenetically derived R. masafuerae harbors a level of genetic variation similar to that of its progenitor, R. evenia. This is the first direct comparison of the genetic consequences of anagenetic and cladogenetic speciation in plants of an oceanic archipelago.